Nujna medicinska stanja v zobozdravstvenih ambulantah - Šink, Žiga (Zdravniški vestnik, 2019)
Recent surveys indicate that dentists individually encounter an average of 2-3 medical emergencies per year. The most common of these include vasovagal syncope, hypoglycaemia, hypertensive crisis and acute asthmatic exacerbation; while other reported emergency presentations, such as anaphylaxis, heart attack and stroke, are far less frequent. Since in general, dentists do not frequently encounter such medical conditions and may not achieve sufficient clinical exposure to foster a sustainable learning effect, regular education and training is imperative on an ongoing basis, in order to maintain the critical knowledge and skill threshold required to effectively deal with medical emergencies. Furthermore, as the British guidelines recommend, each dental office should be adequately equipped to handle all life-threatening medical emergencies, in addition to having an appropriate protocol in place, according to which all the members of the team would act during a medical emergency. Dental offices in Slovenia are not sufficiently equipped with instruments for responding to the spectrum of potential medical emergencies in dental practice. This reality is probably a consequence of insufficient knowledge and lack of clear standards and guidelines regarding the mandatory equipment needs for dental offices.
Keywords: continuing professional development; dentistry; emergency conditions; stalno podiplomsko izobraževanje; urgentna stanja; zobozdravstvo